Features of using silicon carbide in melting converter steel - V. I. Bondar (Литьë и металлургия)
The article discusses the possibility of using silicon carbide as the main component for preliminary deoxidation of a carbonaceous intermediate product when the latter is discharged from the converter into a ladle in order to adjust the costs of tradition‑ ally used deoxidizing materials. It has been established that the use of silicon carbide as a deoxidizer is economically feasible in the smelting of low‑carbon low‑alloy steels of converter production.The method of adding the material is described and the results of the work performed are presented.